An Analysis of Illocutionary Acts Found in The Movie “Toy Story 4” - Yuniar Azzizah Hidayani; Senowarsito Senowarsito; Dyah Nugrahani (Program Studi Pendidikan Guru Sekolah Dasar, Universitas PGRI Semarang, 2023)
The object of this study is a movie called “Toy Story 4.” The data of this study are the utterance of the main characters of this movie who are Woody and Bo Peep. This study are aimed to find the types of illocutionary act found in the movie based on the theory which belongs Searle , to find the most dominant type of illocutionary act which are performed by the main characters of the movie, and to find the contribution of the result of the study in teaching English. This study utilized descriptive qualitative method. Based the result of the research, it is shown that there are five types of illocutionary acts. From the total 417 utterances which contain illocutionary act, there were 164 utterances belong to assertive, 163 utterances belong to directive, 66 utterance belong to expressive, 23 utterances belong to commissive, and 1 utterance belong to declarative illocutionary act. The dominant type of illocutionary acts which are performed by the main characters of the movie “Toy Story 4” – Woody & Bo Peep – are assertive (39,33 % out of 100%), and directive (39,09% out of 100%). In addition, the result of this research can be contributed as a teaching media in teaching English.